Flame temperature distribution from ISO2685 standard propane-air burner using CFD - Bheekhun N.; Abu Talib A.R.; Hasini H.; Hassan M.R. (Trans Tech Publications Ltd, 2023)
This analysis considers the computational simulations of the temperature distribution of a propane-air customary flame combusted from an aeronautical fire-certification set according to the ISO2685standard. The numerical codes have been executed in Computational Fluid Dyanmics using the k-? SST turbulence model coupled with eddy-dissipation. The result shows that the maximum predicted temperature using the standard flame settings exceeds the required temperature for evaluation of a fire-resistive material. The mole fractions of the by-products, carbon dioxide and water have also been predicted. © (2014) Trans Tech Publications, Switzerland.